IMPROVING STUDENTSâ READING COMPREHENSION OF NARRATIVE TEXT BY USING FABLE AT THE GRADE X SMAN 1 BONAI DARUSSALAM - -, Mislaini (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research is conducted in order to improve students Reading Comprehension of Narrative Text ByUsing Fable at The Grade X SMAN 1 Bonai Darussalam. This research used a Classroom Action Research (CAR)which is conducted to solve the students problem in English reading. The Classroom Action Research (CAR). Theresearcher did two cycles in which each cycle consist of planning, acting, observing, and reflecting. The data weregathered through qualitative and quantitative data. The qualitative gained by analyzing the field note, observationsheet and interview. Then quantitative data were obtained from the students writing score of cycle I and cycle II.The finding of this research indicated that the implementation of Fable media was success full since there isan improvement in students reading comprehension in narrative text. The finding showed an improvement instudents reading comprehension of narrative text from the average of reading test narrative text in cycle 1 was 60,85 to 73,50 the average of reading comprehension in cycle 2. Based on the finding mentioned before. The researchersuggests that English teacher could implement Fable material in teaching reading narrative text in order to motivatestudents in learning English reading in narrative text.